Announcements by radio - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
'The radio helped us solve a real problem we d been having in the village. When someone died, it was almost impossible to get in touch and tell relatives, living in villages which are maybe 30 to 40 kilometres away, so that they could come to the...